Alright here is the question

Let A, B, C be subsets of a universal set. Show

A-(B intersection C)= (A-B) union (A-C)

Ok my thoughts, I understand how logically this is true, If you subtract the like terms of B and C from set A it is the same as taking a the union of both.

For instance if A= {1,3} and B= {2,4,7} and C= {3,4,6}. Then A-(B inter C) will equal {-4}+{1,3}. Also i know that A-B union A-C equals the same thing.

Can someone help tell me how to put it in proof form? I know whats going on just not how to say it.